The Use of i-THINK Mapping in Teaching Reading Comprehension among ESL Teachers - Sharif, Siti Rohaya; Swaran Singh, Charanjit Kaur; Ong, Eng Tek; Mulyadi, Dodi; Ichsan, llmi Zajuli; Rahmayanti, Henita; Kiong, Tee Tze (2023)
This study investigated the use of i-THINK Mapping in teaching reading comprehension by ESL teachers to a group of Form Five students, and the factors and challenges the ESL teachers faced in teaching reading comprehension using i-THINK Mapping. A qualitative approach, specifically a case study design, was employed in this study. Classroom observations, semistructured interviews, and document analysis of their lesson plans were used to collect the data. Four ESL teachers with a minimum of 5-year teaching experience in a rural secondary school in Hulu Selangor, Malaysia, were selected using a purposive sampling technique to participate in this study. Thematic analysis was used to analyse the data obtained from classroom observations and interviews. The findings show that the teachers had applied five i-THINK maps, including a Circle Map to define in context, a Bubble Map to describe, a Double Bubble Map to compare and contrast, a Flow Map to show the sequence of an event, and a Tree Map to classify different ideas. The i-THINK Mapping motivated the students to discuss, brainstorm, and cooperate with their peers to detect the details from the given reading texts. The teachers’ challenges include the time constraints in preparing the lesson with i-THINK Mapping and a low level of student English proficiency. One implication of this study is that teachers’ use of i-THINK Mapping to teach reading comprehension could assist students in generating ideas, expanding ideas, and expressing them orally.